Improving and evaluating the adhesion and stability of make‐up by enhancing the affinity between skin/make‐up layer. Issue 1 (29th August 2021) - Jeon, Hyungjoon; Kwon, Tae Geun; Shin, Yong Won; Cho, Yeeun; Yang, Hyunmi; Park, Sang‐Wook; Song, Young‐Sook
Abstract: Purpose: Make‐up clumps, bumps and collapses are the three factors that determine how well make‐up has been performed. The purpose of this study is to reduce the three factors mentioned above by using amphiphilic substances to increase the affinity between the skin and the make‐up layer. In addition, it aims to evaluate the improvement of the make‐up layer by developing an objective make‐up layer evaluation method. Methods: Experiments were performed in an attempt to increase the affinity between the skin and the make‐up layer by minimizing the difference in surface energy between the two. Multiple types of artificial skin (leather and bio‐skin) were used and treated to form the liquid foundation layer. Qualitative evaluation of the make‐up layer was conducted by analyzing the surface, cross‐section, and fracture area of the make‐up layer, using the evaluation method proposed in this study. Results: After applying this method and taking measurements by 3D surface analysis, the surface roughness of the make‐up layer reduced by 46%, and the maximum thickness of the make‐up layer reduced by about 50% in comparison with the control group (method not applied). In the case of the make‐up layer to which this method was applied, two‐dimensional cross‐sectional Scanning Electron Microscope (SEM) image analysis confirmed that agglomeration was reduced, and the thickness of the make‐up layer was also reduced by an average of 54%. According to this result, the technique of increasing the affinity between the skin and the make‐up layer reduces the level of aggregation of make‐up and encourages the formation of a uniform and thin make‐up layer. Also, the fracture area after motion simulation was reduced by 33%. These results indicate that the method of increasing the affinity between skin/make‐up membranes positively affects the formation of a uniform make‐up layer. Conclusion: Increasing the affinity by reducing the surface energy between the skin and the make‐up layer plays an important role in forming a thin and uniform make‐up layer by improving the problems of lifting, agglomeration, and collapse of the make‐up. In addition, it has been confirmed that through this method, the quality of consumer experience related to make‐up satisfaction can be improved. The results show that objective analyses of make‐up help the understanding of the quality of consumer experience on make‐up.